Anne Shirley’s Character Development and its Causes as Seen in Anne of Green Gables by Lucy Maud Montgomery - Fatimah Salsabila Az-Zahra; Nur Saktiningrum (Lexicon, 2019)
This research discusses the character development of Anne Shirley, the main character of the novel Anne of Green Gables by Lucy Maud Montgomery. The objective of the research is to understand the character development of Anne Shirley and also examines the factors that cause development. The analysis is conducted by using the objective approach by M.H Abrams because the approach is suitable to analyze character, characterization, and character development. The result of this research shows that the character of Anne Shirley is developed from a loveless girl to a mature teenager. Her character development is caused by two factors, internal factor which is her own motivation and external factors which come from the people around her and new environment.